Retrieving particulate matter concentrations over the contiguous United States using CALIOP observations. (1st April 2022) - Toth, Travis D.; Zhang, Jianglong; Vaughan, Mark A.; Reid, Jeffrey S.; Campbell, James R.
Abstract: Using twelve years (2007–2018) of NASA Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP) near-surface 532 nm aerosol extinction retrievals, multi-year mean and trends of particulate matter (PM) concentrations are derived over the contiguous United States (CONUS). Different from past studies that use column integrated aerosol optical thickness, here only near-surface CALIOP aerosol extinction is used for deriving near-surface PM with aerodynamic diameters less than 2.5 μm (PM2.5 ) concentrations using an innovative, bulk-mass-modeling-based method. Compared against ground based PM2.5 measurements from the U.S. Environmental Protection Agency (EPA), an encouraging relationship between CALIOP-derived PM2.5 and EPA-observed PM2.5 (Deming slope = 0.89; RMSE = 3.42 μg/m3; mean bias = −1.00 μg/m3) is found using combined daytime/nighttime CALIOP data. Also, comparable trends in PM2.5 concentrations from the EPA and daytime and nighttime CALIOP data are found for most of the eastern CONUS and imply that air quality is generally improving over this region for the study period. Over the western CONUS, a seasonal analysis reveals that PM2.5 trends are positive during the more active wildfire season (June through November) but negative for other months. This study suggests that lidar data show promise in their use for obtaining PM2.5 estimates and provides motivation to further explore aerosol extinction-based PM concentration retrievals in anticipation of future space-based lidar missions. Highlights: PM2.5 concentrations are derived over CONUS using CALIOP aerosol extinction retrievals. CALIOP-derived PM2.5 trends are compared against EPA-based in situ PM2.5 trends. A decreasing pattern in PM2.5 (air quality improvement) over eastern CONUS is found. Over western CONUS, PM2.5 levels trend upward during the more active wildfire season.